PENGARUH KUALITAS PRODUK KARTU INDOSAT IM3 TERHADAP LOYALITAS PELANGGAN PADA MAHASISWA DI SURABAYA - Irawan, Wahyu; Mulyati, Awin; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2015)
Goals to be achieved in this study was to determine the effect of product quality to customerLoyalty cards Indosat IM3 student in Surabaya.              The research proves that F count> F table (14.108> 2,311) or in other words together performance, features, reliability, service ability can influence customer loyalty. While the test (R2) together - together amounting to 42.9% and the remaining 57.1% were influenced other variables outside the research. The study also proves that partially, performance, features, reliability, service ability significant effect on customer loyalty because each independent variable is the performance, features, reliability, service ability have thitung> tabel.